MEMBANGUN BUDAYA HIDUP BERSIH DAN SEHAT DI SEKOLAH DASAR 009 SAMBUTAN KELURAHAN MAKROMAN DENGAN MEMANFAATKAN MEDIA POSTER - Nursilviani; Mahkamah Brantasari (Fakultas Keguruan dan Ilmu Pendidikan Universitas Widya Gama Mahakam Samarinda, 2022)
Cleanliness and health are two things that need to be considered by Indonesia. Recognizing that Indonesia is still very far behind in these two fields requires self-awareness regarding the urgency of hygiene and health issues. The community service activities carried out at SD 009 Sambutan, Makroman Village are a small step that must be taken as an example and habituation to a culture of clean and healthy living to improve the level of hygiene and health in Indonesia as well as efforts to build a young generation with character. The method used in this activity is socialization by way of lectures and providing information through the use of posters. The material presented was in the form of recommendations on how to implement the four activities in the form of eating healthy food, maintaining personal hygiene, maintaining a clean environment and also the importance of exercising, with this socialization it is hoped that it will be able to build a generation of young people with character as well as improve the level of cleanliness and health of Indonesian children in the eyes of the world.